Social Time and the Economics of Science - Emil Dinga (Amfiteatru Economic Journal, 2022)
The purpose of the paper is to propose and examine a logical and epistemological tool to measure science as a specific human activity in the social cooperation network. In preparing the very approach of the main issue of the research, a short examination of the concept and typology of science is presented, including Economics. The basic target of the paper is to find and examine a structurally (as deep as possible) variable holding the potential to ensure (as a common measure, perhaps of quantic, i.e., discrete nature) the commensurability of any science. Such a tool is considered to be a species of time, that is, the social time. Essentially, it is shown that science provides a specific outcome, namely, the social time variation, which constitutes the fundamental input to any (other than science) social action/activity. This outcome is treated from an Economics account (not quite the standard Economics, but the evolutionary one), so that one can discover all implications of science(s) from an economic point of view (including, for example, the social entropy affected by the science realm). Finally, the paper proposes a sui generis market structure and functioning – the science market, including the Kuhnian paradigm, to provide a general description (both causal and pure functional) of the Economics of science.
Keywords: A10; A12; B41; 330; sciences; social time; social time entropy; science market; economics of science.